KAUSALITAS DAN INDEKS HARGA SAHAM 11 NEGARA TERHADAP INDEKS HARGA SAHAM INDONESIA - Ahmadi Ahmadi (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2016)
This research aims to prove the relationship of reciprocity between the stock prices index in 11 countries (Singapore, Malaysia, Thailand, the Philippines, South Korea, Hong Kong, Japan, Taiwan, Australia, London and NYSE) as well as stock price index korelasinya 11 countries with Indonesia stock price index. In this research using statistical methods, namely: test the Granger Causality and Bivariate Correlation. Variable sample used consists of stock price index in 12 countries. Research results using test Dickey Fuller pointed out that the original data on the level of zero stationer with a confidence level of 99%. The results of the research there is a trade-off between the price index stocks on 11 countries against Indonesia's share price index that is only on the Hong Kong stock index, and from all countries who were the object of this research have a significant correlation with Indonesia stock index.Keywords: Exchange Rate, Stock Price Index